ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL (RGEC) YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Studi Kasus Pada Bank Tabungan Negara (Persero) Tbk Periode 2023) - Erni Ayu Nindiya; Ihwan Satria Lesmana; Ombi Romli (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
In building trust in the banking world competition, bank health is very important for the bank, because customer trust and loyalty to a bank can be factors that can support and facilitate the bank in developing business strategies. This study aims to determine the level of bank health at PT Bank Tabungan Negara (Persero) Tbk for the 2023 period.This research method is descriptive with a qualitative type. The data source for this study is secondary data. The secondary data used is the Annual Financial Report of PT Bank Tabungan Negara (Persero) Tbk for the 2023 period. The results of the study on the level of health of PT Bank Tabungan Negara (Persero) Tbk for the 2023 period in terms of the Risk Profile factor, as measured by the bank's Non-Performing Loan financial ratio, are included in the healthy category and the Loan to Deposit Ratio financial ratio is included in the fairly healthy category. From the Good Corporate Governance factor, it is in the healthy or good category. Based on the Earnings factor, as measured by the Return On Assets ratio, it is categorized as fairly healthy. Finally, from the Capital factor, using the Capital Adequacy Ratio ratio, it is considered very healthy.Based on the results of research conducted at the banking company PT Bank Tabungan Negara (Persero) Tbk for the 2023 period using the RGEC method, it can be concluded that BTN's health level is at PK-2 (healthy) with a ratio of 76%.